The Effect of RBA OSS-Based Company Licensing on Domestic Investment - Raras Nadifah Cahyaningtyas (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As an embodiment of Law Number 11 of 2020 concerning Job Creation (UU CK) which prioritizes improving the investment ecosystem and business activities as well as Government Regulation (PP) Number 5 of 2021 concerning the Implementation of Licensing Risk-Based Business, business licensing in Indonesia has undergone significant reforms in order to keep attracting investors. In particular, domestic investment is of greater concern because it will encourage job creation. When people have got a job, of course the income will increase. When people's incomes increase automatically this encourages an increase in consumption. In this paper, the author hopes that the reader can find out the importance of the influence of domestic investment. In particular, after the simplification of the company's licensing system, it became a Risk-Based Business Licensing or OSS RBA (Online Single Submission Risk Based Approach).